Vamos a leer sobre-- Abraham Lincoln - Black, Sonia; Heyer, Carol, 1950- (New York : Scholastic, 2002)
A brief biography of the sixteenth president of the United States, Abraham Lincoln, who led the country through the difficult times of the Civil War.
"Cartwheel books."
"Mariposa, Scholastic en espanol"--P. [4] of cover.
In Spanish.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Spanish language materials; Spanish language materials; Materiales en espanol